ISLAM, KESEHATAN DAN LINGKUNGAN HIDUP: Studi Tentang Jamu Madura - Handayani, Sri (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
AbstracIslamic teaching, to maintain quality of healthy life, has inspired Madurese. This island has treasure of culture that harmonizesÂ  Islamic credo. This article studies peopleâs notion on Madurese herbal ingredients, the existence of Madurese herbsÂ  in dealing with environment conservation, socio-cultural value, and todayâs people perception toward Madurese herbs. The result of study shows that Madurese herbs has been the work of Madurese ancestors and piece of traditional treasury to keep a healthy life. Presently, it is assumed that Madurese herbs hold up the harmony of husband and wife intimate relationship.Â  This is undeniable fact but Madurese herbs also enclose the other restorative power instead.Â  The cultivation of Madurese herbal ingredients will give a good impact to the effort of environment conservation.Â  This is also expected to preserve the drinking help tradition as a medium to have a healthy life. To conserve environment means to obey the Islamic teachingKata-kata Kuncijamu Madura, lingkungan hidup, sosial-budaya